Analisis Yuridis Kekuatan Pembuktian Tangkapan Layar sebagai Alat Bukti Elektronik dalam Perkara Perceraian (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2026)
Digital evolution in the pattern of social interaction of the community also has a significant influence on the dynamics of the national judicial system. The transformation covers all judicial sectors, both religious and public, especially related to the technique of presenting evidence in the litigation process. This research is carried out with normative legal methods and is descriptive analytical. The author utilizes secondary data obtained through library search, which is then processed with qualitative normative analysis techniques. The legitimacy of screenshots as evidence has been explicitly regulated in applicable regulations. Referring to the renewal of the ITE Law in Law Number 1 of 2024, Article 5 paragraph (1) affirms that electronic information and its printed results are recognized as valid evidence before the law. This study shows that normatively, screenshots have a strong legal position in the civil system. However, in the reality of the trial, this instrument is positioned as a free evidence (vrij bewijs), which means that the weight of the evidence is not absolute and depends on the judge's evaluation and conviction.